AURAS, Marli. Guerra do Contestado: a organização da irmandade cabocla. Florianópolis, Ed, UFSC, Assembléia Legislativa, 1984. 204p., il. - Brancato, Sandra Maria Lubisco (Estudos Ibero-Americanos, 1985)
-